Pengaruh Presbikusis Terhadap Kualitas Hidup Lansia - Ellysa Angguman Putri; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Presbycusis is a sensorineural hearing loss that commonly occurs in the elderly as a result of the degenerative process of the hearing organ which continues to decrease progressively and symmetrically on both sides of the ear. Based on the results of audiometric examination and temporal bone pathology, presbycusis can be classified into four categories are sensory type, neural type, metabolic type, and cochlear conduction types. Factors involved in the development of presbycusis are genetic factors and environmental factors. Presbycusis is an important problem in the elderly social interaction. The elderly rely on their hearing to overcome the limited vision that is starting to get impaired. In addition, decreased concentration and memory due to age also make it difficult for the elderly to understand speech, especially in noisy situations. Presbycusis can cause serious complications, such as anxiety disorders, communication disorders, depression, isolation, and cognitive disorders. Presbycusis can affect all aspects of life, especially the personal and daily life. This is because hearing is an important sensation for the elderly in improving the quality of life, maintaining safety and health. Communication barriers caused by presbycusis affect the quality of life of the elderly.